The Goods Categorization Layout for Reducing Time Spent on a Reach of Goods: A Case Study of AAA Company - Tantijirasakun, Chalalai; Hotrawaisaya, Chattrarat (Journal of Innovation and Management, 2020)
The purposes of this study were 1) to make an analysis on goods positioning of ABC type within the warehouse; 2) to layout the warehouse; and 3) to reduce time spent on each reach of goods. The data were collected from 50 samples, who were the company’s staff working within the chosen warehouse. A questionnaire was employed as an instrument. The data then were analyzed by calculating the frequency, percentage, average, and standard deviation (S.D.). The study results indicated as follows: 1) An analysis on goods positioning of ABC type: The percentages of goods were 35 for Group A (targeted at kids and teenagers), 41 for Group B (teenagers and women’ clothes), and 25 for Group C (shows and souvenirs). The goods were categorized that way for an ease of positioning, depending on how frequently those goods have been reached, 2) The warehouse layout: Three types of warehouse layout were explored. (1) The present layout of warehouse: Group B’s goods were placed in the front, followed by the A’s and C’s respectively. (2) The ABC-horizontally-positioned layout of warehouse: The A’s goods were placed in the front near the quality-check dock. This was suitable as the products have been distributed in a short duration; so have the B’s goods. Both of the groups contained goods of high flow and distributed nearly most frequently, so the positions of them were deemed crucial. Compared to the formers, the C’s were least frequently reached and therefore placed inside at the center instead so there could be a greater space in the front. This would also bring an ease of process when the new arrivals were received. (3) The ABC-vertically-positioned layout of warehouse: Positioning the A’s goods in a vertical row near the check deck could provide a shorter distance and help reduce time. Also, it could be easier to observe the staff’s performance in overall and remain a wider space in the front of thewhich additionally simplified the process of receiving and distributing goods as well. For the B’s goods, they were put behind the A’s and followed by the C’s, which were all positioned based on their frequency of reach, and 3) An effective layout of warehouse could help reduce some time spent on a reach of goods. Therefore, it is safe to make an analysis on goods categorization. Locating each zone properly is an influential variable for making a plan for hallways within the warehouse. Performing so precisely helps reduce time when searching for goods and allows individuals to reach each of them faster. Moreover, the state that staff can store the goods and return them to the labelled zone correctly contributes a lot to the flow of work and the staff’s performance, resulting in the work efficiency. warehouse,